The concept of environmental rights - Mohd Anuar, Haslinda (2013)
The relationship between human and environment was first introduced in the declaration of the United Nations Conference on the Human Environment 1972. Later, the Rio Declaration 1992 strengthens the relationship with the concept of sustainable development. However, the word of 'environmental rights' was not explicitly mention. Examining both susbstantive and procedural environmental rights, this paper discusses the concept and recommends the practicability of having it.